(untitled) (Bangladesh Journal of Botany, 2021)
A pot culture experiment was carried out under controlled conditions for the detailed study of morphophysiological and advanced stress response adaptive mechanisms along with yield performance of pea varieties under the influence of seed priming substances. The performances of selected seed priming substances in different pea varieties were tested with water stress. Growth and physiological parameters documented at the stress period. From the experiment, it can be inferred that seed priming substances like KH2PO4 (1.5 and 3%), H2O2 (10 mM) and PEG (5%) were significantly outperformed in inducing higher growth with positive physiological changes. Bangladesh J. Bot. 50(2): 199-208, 2021 (June)